Effect of HMGCR Variant Alleles on Low-Density Lipoprotein Cholesterol-Lowering Response to Atorvastatin in Healthy Korean Subjects - Chung, Jae Yong; Cho, Sung Kweon; Oh, Eun Sil; Lee, Dong Hwan; Lim, Lay Ahyoung; Jang, Seong Bok; Lee, Yoon Jung; Park, Kyungsoo; Park, Min Soo (Journal of clinical pharmacology, 2012)
The investigators quantified the relationship between the genetic polymorphism of HMGCR (3-hydroxy-3-methylglutaryl coenzyme A reductase) and the low-density lipoprotein cholesterol (LDL-C)–lowering effects of atorvastatin in a prospective clinical study. Twenty-four healthy participants were grouped into HMGCR rs3846662 GG (n = 13) and AA (n = 11) genotypes and given atorvastatin (20 mg/d) for 14 days. Serum levels of LDL-C, high-density lipoprotein cholesterol, total cholesterol, triglycerides, and creatinine kinase (CK) were measured before (day 1) and 7, 13, 14, 15, 16, 21, and 28 days after dosing initiation. Blood samples for pharmacokinetics were taken on days 14 through 16. The levels of LDL-C in the GG group were significantly higher than in the AA group at all observation times, with mean differences of 18% to 33% (P < .05). The area under the LDL-C–time curve and the minimum value of LDL-C in the GG group were 24% and 23% higher than in the AA group, respectively (P < .01). There was no significant difference in other lipids, CK, and pharmacokinetic parameters. The HMGCR rs3846662 GG genotype was quantitatively documented to be a significant determinant for higher LDL-C level in basal state and possibly in response to atorvastatin.